Willingness to pay framework : climate change mitigation in households - Streimikiene, Dalia; Mikalauskiene, Asta (Boca Raton : CRC Press, 2021)
"This book aims to develop a framework for the assessment of population preferences in climate change mitigation policies by applying Willingness to Pay (WTP) approach and presents the results from several case studies in Lithuania on renewable energy generation and renovation in different households. These analyses of climate change mitigation policies and measures, based on the assessment of their effectiveness, provide recommendations for developing innovative measures in other countries. Since public preferences are variable, climate change mitigation policies can change these preferences and allow to form new ones. A useful reference for academics, policy makers, and business community"--
OCLC-licensed vendor bibliographic record.
Keywords: Climate change mitigation -- Social aspects -- Case studies; Climate change mitigation -- Social aspects -- Lithuania; Willingness to pay -- Case studies; Willingness to pay -- Lithuania; BUSINESS & ECONOMICS / Development / Sustainable Development